2008
DOI: 10.1007/s00192-008-0640-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of interstitial cystitis with hydrodistention and bladder training

Abstract: This study aimed to evaluate the efficacy of hydrodistention (HD) and bladder training for interstitial cystitis (IC). From 1997 to 2006, 361 consecutive IC patients were treated by HD, followed by bladder training. Each patient was followed up using a diary for 8 weeks after HD weekly and monthly thereafter. The efficacy of the treatment was evaluated using the average of the voided volumes and the voiding frequency. The mean +/- standard deviation of the pre-HD daytime voided volumes and voiding frequency we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Improvement in patient symptoms following HD has been documented for many years, but the duration of treatment effect appears to be limited [70]. In a recent study combining HD with bladder training, 51.2% of patients experienced remission of symptoms, suggesting that bladder training may significantly improve bladder capacity and subsequently, bladder functioning [71].…”
Section: Bladder Hydrodistentionmentioning
confidence: 99%
“…Improvement in patient symptoms following HD has been documented for many years, but the duration of treatment effect appears to be limited [70]. In a recent study combining HD with bladder training, 51.2% of patients experienced remission of symptoms, suggesting that bladder training may significantly improve bladder capacity and subsequently, bladder functioning [71].…”
Section: Bladder Hydrodistentionmentioning
confidence: 99%
“…The therapeutic efficacy of hydrodistension has been investigated with varying rates and durations of effect observed [24][25][26][27][28]. The results of those studies, however, were drawn from patients undergoing cystoscopic hydrodistention to maximum anesthetic capacity under general or epidural anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 40.2% and 36.3% of the patients indicated that their IC symptoms deteriorated right before and after menstruation, respectively. 34 Report of pain persisting after intercourse occurs in 46%-53% of patients. 8 As mentioned previously, symptom flares are often associated with sexual relations, menstrual cycle, certain types of foods, and stress.…”
Section: Patient Historymentioning
confidence: 99%
“…Moreover, at 2 months after HD, more than 80% of the IC patients who had suffered flares during menses and coitus reported a significant reduction in these symptoms. 34 In younger women, a retrospective review of 18 patients aged 15-25 showed 11 patients had HD alone, of whom 6 improved, 2 reported no change, 1 reported exacerbation, and 2 had insufficient data charted. In 10 women who had repeat HD, the mean time to repeat cystoscopy was 17 months.…”
Section: Hydrodistentionmentioning
confidence: 99%
See 1 more Smart Citation